THE RELATIONSHIP OF MATERNAL SELF MANAGEMENT AND ATTITUDES OF PREGNANT WOMEN IN PREVENTING OF STUNTING AT THE CLINIC OF KASIH IBU DELITUA IN 2023 - PURBA, RENTAWATI; BARUS, DEWI TIANSA (Jurnal Penelitian Keperawatan Medik, 2023)
Background: Stunting is a body height age, due to a lack of nutritional intake for a long time, causing chronic malnutrition problems. This study aimed to determine maternal self-management and the attitude of pregnant women in preventing stunting in pregnant women in the third trimester of pregnancy at Clinic of Kasih Ibu Deli Tua, Deli Serdang. Method: The study method was personal correlation and cross sectional study design. The sample of this study was 81 respondents with the sampling technique being as total sampling. Result: The results of the chi square statistical test carried out obtained a significant number or p value (value=0.000) Conclusion: The importance of maternal attitudes in preventing stunting is to prevent growth disorders of children so that it can be increased their growth and development